Sosialisasi Pola Asuh Anak dan Remaja di Era Digital (PAAREDI) - Harianto Harianto; Zulin Nurchayati; Alfiana Yuniar Rahmawati (Jurnal Karya untuk Masyarakat (JKuM), 2025)
This Community Service (PkM) activity is motivated by the phenomenon of technologyaddiction such as gadgets, social media, the internet and online games among children andteenagers. This phenomenon is a new challenge that parents as part of the closest family mustpay attention to. Parents need to adapt to changes in the digital era and understand emergingtrends in order to optimize balanced parenting. Therefore, PkM with the theme "Socialization ofParenting Patterns for Children and Adolescents in the Digital Era (PAAREDI)" has beencarried out to empower the role of parents in carrying out parenting patterns in a loving,inclusive, communicative and supportive manner in the digital era. PkM activities were carriedout using the counseling or socialization method which was attended by 150 PKK cadres inBalerejo Village, Kebonsari District, Madiun Regency. The PkM results show that all PKKcadres gain knowledge and understanding of the importance of education and parentingpatterns for children and teenagers by families in their environment. Apart from that, PkMactivities are also needed by PKK cadres to be able to intensify family character education inorder to encourage the creation of a family of faith, noble and virtuous morals.